SCOMBROID SYNDROME − CASE REPORTS - Neja Roškar; Zdravko Roškar (The Society for Children with Metabolic Disorders, 2020)
Scombroid syndrome, or histamine poisoning, results from the consumption of inadequately preserved and improperly frozen fish as well as contaminated cheese. It most commonly presents with sudden redness of the face and neck, an erythematous rash, urticaria, diarrhoea, and headache, usually soon after the consumption of contaminated food. It is often misdiagnosed as a seafood allergy since the clinical picture is similar. The condition is usually self-limiting. If treatment is necessary, H1 and H2 antihistamines are usually sufficient. In this article, we present two paediatric cases of the scombroid syndrome, which were discovered due to a similar epidemiological history.